Unravelling the role of fatty acid metabolism in cancer through the FOXO3-FOXM1 axis. (15th February 2018) - Saavedra-García, Paula; Nichols, Katie; Mahmud, Zimam; Fan, Lavender Yuen-Nam; Lam, Eric W-F.
Abstract: Obesity and cachexia represent divergent states of nutritional and metabolic imbalance but both are intimately linked to cancer. There is an extensive overlap in their signalling pathways and molecular components involved such as fatty acids (FAs), which likely play a crucial role in cancer. Forkhead box (FOX) proteins are responsible of a wide range of transcriptional programmes during normal development, and the FOXO3-FOXM1 axis is associated with cancer initiation, progression and drug resistance. Free fatty acids (FFAs), FA synthesis and β-oxidation are associated with cancer development and progression. Meanwhile, insulin and some adipokines, that are up-regulated by FAs, are also involved in cancer development and poor prognosis. In this review, we discuss the role of FA metabolism in cancer and how FA metabolism integrates with the FOXO3-FOXM1 axis. These new insights may provide leads to better cancer diagnostics as well as strategies for tackling cancer development, progression and drug resistance. Highlights: Fatty acids (FAs) play a crucial role in cancer. The FOXO3-FOXM1 axis promotes cancer initiation, progression and drug resistance. FFA, FASN and β-oxidation are associated with cancer development and progression through the FOXO3-FOXM1 axis. Insulin and some adipokines are related with cancer development and poor prognosis. The link between FOXO3-FOXM1 axis and FA metabolism could be targeted to improve cancer prevention, diagnosis and treatment.